2017
DOI: 10.3390/rs9010047
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Aboveground Biomass in Tropical Forests: Field Methods and Error Analysis for the Calibration of Remote Sensing Observations

Abstract: Mapping and monitoring of forest carbon stocks across large areas in the tropics will necessarily rely on remote sensing approaches, which in turn depend on field estimates of biomass for calibration and validation purposes. Here, we used field plot data collected in a tropical moist forest in the central Amazon to gain a better understanding of the uncertainty associated with plot-level biomass estimates obtained specifically for the calibration of remote sensing measurements. In addition to accounting for so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 60 publications
(117 reference statements)
4
28
0
2
Order By: Relevance
“…Our limited error analysis indicated that random variations in tree diameter and stand density caused the largest uncertainty with our estimates of Δ C w (Table ). Overall, mean (+ SD ) uncertainty associated with the measurement of tree dimeter and stand density was approximately 15 + 3 and 24 + 5%, respectively, which is comparable to that estimated in other studies (Gonçalves et al, ), and the relative uncertainty associated with estimating stand density increased somewhat as mean stand density increased.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our limited error analysis indicated that random variations in tree diameter and stand density caused the largest uncertainty with our estimates of Δ C w (Table ). Overall, mean (+ SD ) uncertainty associated with the measurement of tree dimeter and stand density was approximately 15 + 3 and 24 + 5%, respectively, which is comparable to that estimated in other studies (Gonçalves et al, ), and the relative uncertainty associated with estimating stand density increased somewhat as mean stand density increased.…”
Section: Discussionsupporting
confidence: 79%
“…There are many possible sources of uncertainty with estimating of C w , including measurements of D BH , wood density (ρ), and stand tree density (D s ), and estimating tree height (h) from D BH (Chave et al, 2005;Clark, Brown, Kicklighter, Chambers, Thomlinson, Ni, & Holland, 2001;Gonçalves et al, 2017;Marthews et al, 2012). We used bootstrapping to quantify the random uncertainty associated with estimating D BH , ρ, D s , and h and the cumulative effect of this uncertainty on calculating AGC and C w .…”
Section: Discussionmentioning
confidence: 99%
“…The scatter of the red points about the dashed line of Figure 9 is 0.3 Mg-ha −1 -m −1 , which, when multiplied by the average phase-height rate (from Table 1) of 0.5 m-yr −1 yields a 0.15 Mg-ha −1 -yr −1 systematic effect. This scatter is in part due to the error in measured AGB of 25% [24]. In looking up a plot's AGB/h φ , a 25% error will be made in the AGB argument of (13).…”
Section: The Performance Of Phase-height and Agb Rate And Future Enhamentioning
confidence: 99%
“…The diameter, height, and wood density were used with allometric equations [23] to estimate AGB. The accuracy of the AGB estimates was 25% [24]. Plots were geolocated with sub-meter accuracy using differential GPS and a total station.…”
Section: Tapajós National Forest and Field Measurementsmentioning
confidence: 99%
“…Hence, the objective of this paper was to determine the economic value of carbon stock and carbon sequestration in a dipterocarp tree dominated forest. The methods to determine carbon stock include forest inventories with allometric tree biomass regression models (Foody et al 2001;Gonçalves et al 2017;Lu 2005). Hence, such data is important for managing forested areas for reducing and mitigating CO 2 emission (Van Breugel et al 2011).…”
Section: Introductionmentioning
confidence: 99%